Influence of case definition on incidence and outcome of acute coronary syndromes. Issue 2 (30th December 2016) - Torabi, Azam; Cleland, John G F; Sherwi, Nasser; Atkin, Paul; Panahi, Hossein; Kilpatrick, Eric; Thackray, Simon; Hoye, Angela; Alamgir, Farqad; Goode, Kevin; Rigby, Alan; Clark, Andrew L
Abstract : Objective: Acute coronary syndromes (ACS) are common, but their incidence and outcome might depend greatly on how data are collected. We compared case ascertainment rates for ACS and myocardial infarction (MI) in a single institution using several different strategies. Methods: The Hull and East Yorkshire Hospitals serve a population of ∼560 000. Patients admitted with ACS to cardiology or general medical wards were identified prospectively by trained nurses during 2005. Patients with a death or discharge code of MI were also identified by the hospital information department and, independently, from Myocardial Infarction National Audit Project (MINAP) records. The hospital laboratory identified all patients with an elevated serum troponin-T (TnT) by contemporary criteria (>0.03 µg/L in 2005). Results: The prospective survey identified 1731 admissions (1439 patients) with ACS, including 764 admissions (704 patients) with MIs. The hospital information department reported only 552 admissions (544 patients) with MI and only 206 admissions (203 patients) were reported to the MINAP. Using all 3 strategies, 934 admissions (873 patients) for MI were identified, for which TnT was >1 µg/L in 443, 0.04–1.0 µg/L in 435, ≤0.03 µg/L in 19 and not recorded in 37. A further 823 patients had TnT >0.03 µg/L, but did not have ACS ascertained by any survey method. Of the 873 patients with MI, 146 (16.7%) died during admission and 218 (25.0%) by 1 year, but ranging from 9% for patients enrolled in the MINAP to 27% for those identified by the hospital information department. Conclusions: MINAP and hospital statistics grossly underestimated the incidence of MI managed by our hospital. The 1-year mortality was highly dependent on the method of ascertainment.